Social capital among agricultural producers in the Czech Republic: its impact on economic performance; Sozialkapital landwirtschaftlicher Produzenten in der Tschechischen Republik: Seine Auswirkung auf das ökonomische Ergebnis - Axel Wolz; Jana Fritzsch; Jitka Pencáková (Leibniz Institute of Agricultural Development in Central and Eastern Europe (IAMO), 2006)
The change of the political regime from the socialist central planning system to a market economy and pluralistic society required the reorganisation not only of agricultural production, but also of the organisations in their support. In the Czech Republic, agricultural production is characterised by a dualistic structure in these days, i.e. private farmers on the one side and corporate farms on the other. However, among both groups some had been economically more successful than others. In general, a varying adoption of production factors, i.e. land, labour and capital is identified as being of influence. Whether their ability to collaborate with other farms is an additional factor, which has been discussed under the concept of social capital since quite some time, will be analysed in this paper. Based on the findings of a survey among a sample of 62 farms by adopting factor and multiple regression analysis it can be deduced that social capital is indeed a significant factor determining the level of farm income. – – Der Systemwechsel von 1989 erforderte auch in der Tschechischen Republik eine Neuorganisation nicht nur der landwirtschaftlichen Produktion, sondern auch der Organisationen zur Unterstützung der landwirtschaftlichen Produzenten. In diesen Tagen ist die landwirtschaftliche Produktion durch eine ausgeprägte Zweiteilung charakterisiert: Große juristische Personen auf der einen Seite sowie relativ kleine Privatbetriebe auf der anderen. Allerdings sind innerhalb dieser beiden Gruppen große Unterschiede in Hinblick auf den wirtschaftlichen Erfolg zu beobachten. Gewöhnlich wird dies mit einem unterschiedlichen Einsatz der traditionellen Produktionsfaktoren Boden, Arbeit und Kapital erklärt. Ob die Fähigkeit, sich mit anderen Betrieben auszutauschen und zusammenzuarbeiten, einen zusätzlichen Erklärungsfaktor darstellt, wird seit einiger Zeit unter dem Konzept des Sozialkapitals diskutiert. Dies wird hier analysiert. An Hand einer Befragung von 62 tschechischen Betriebsleitern kann mit Hilfe einer Faktoren- und Regressionsanalyse nachgewiesen werden, dass Sozialkapital einen wichtigen Einflussfaktor auf das landwirtschaftliche Einkommen darstellt.
urn:nbn:de:gbv:3:2-898
Keywords: C31; P32; Q12; Z13; 330; Corporate farms; private farms; social capital; cross sectional models; Czech Republic; Landwirtschaftliche Großbetriebe; Familienbetriebe; Sozialkapital; Tschechische Republik.